2017
DOI: 10.5539/gjhs.v9n7p87
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Anemia Levels in Infants and Children in High Altitude Peru

Abstract: When prevalence rates of anemia exceed 40%, the World Health Organization recognizes this as a severe public health problem. In Peru, approximately 43.5% (urban) and 51.1% (rural) of children between the ages of 6 and 36 months have anemia. Currently, limited data exists regarding prevalence rates in many of the high altitude regions of Peru. The main purpose of this pilot study was to establish evidence of anemia in infants and children (7 months through 5 years of age) living in the rural, mountainous region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
2
5
0
1
Order By: Relevance
“…These findings are in accordance with previous studies in a variety of health outcomes (41)(42)(43). The lack of association between travel time to HCF and anemia prevalence observed in this study may be related to the interaction of many structural factors as described in previous studies (44,45).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in accordance with previous studies in a variety of health outcomes (41)(42)(43). The lack of association between travel time to HCF and anemia prevalence observed in this study may be related to the interaction of many structural factors as described in previous studies (44,45).…”
Section: Discussionsupporting
confidence: 93%
“…However, these results could be due to the influence of the geographic location, economic status, and nutritional determinants, besides the quality of access to health services. 22 A study performed in La Paz, Bolivia, shows the prevalence of anemia at 22%, 31% and 15% respectively, in the Camacho, Ingaví, and Murillo provinces, located at similar geographic altitudes as the Añaspamba, somewhat in accordance with our finding. 23 Not corresponding to our results, an investigation via three national nutrition surveys fails to show any difference in the prevalence of anemia in children or adolescents, among the different geographic regions in Mexico.…”
Section: Añaspamba N (%)supporting
confidence: 91%
“…Findings of higher rates of anemia in higher altitude areas correlate to the results found by Amerson et al, who found that 47.5% of 160 participants aged seven months to six years from a high altitude region of Peru had anemia. [12] Both poor nutrition and sanitation likely factors into the high rates of anemia, suggested by common complaints of gastritis and parasitic disorders. Several studies estimate that 80% of the population is infected with H. pylori in Latin America.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Anemia in Peruvian children is also more common at high altitudes compared to lower altitudes. [12] The World Health Organization (WHO) notes that rural areas continue to face inequality in lower distribution of health workers compared to coastal areas. [4] The goals of this preliminary study are to characterize the health conditions of the local populations of CA and SV.…”
Section: Introductionmentioning
confidence: 99%